Kepemimpinan dalam Pendidikan Islam di Era Modern - Dinar Sanjaya; Arief Tirtana (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines leadership in Islamic education in the modern era, focusing on the concepts, strategies, and challenges faced by leaders. Islamic education emphasizes not only academic development but also the cultivation of character, ethics, and spirituality among students. The modern era demands leadership that is adaptive, innovative, and visionary, while simultaneously balancing Islamic values with the demands of technology and globalization.The study employs a qualitative approach through a literature review to analyze leadership theories, the roles of leaders, challenges, and effective strategies. The findings indicate that effective leadership integrates Islamic principles with transformational, visionary, and participative leadership theories, ensuring that educational institutions remain relevant, adaptive, and sustainable. This study contributes both theoretically and practically to the development of contemporary Islamic education leadership.